Analisis Aktivitas VAT Evasion Di Indonesia Dan Strategi Penanganannya - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
Value Added Tax (VAT) is probably the best tax ever invented. Now more than 150 countries worldwide have adopted VAT. The VAT proponents claims that VAT is an effective tax to raise tax revenue of government. Like other taxes, VAT is highly vulnerable to evasion. The potential and the great contribution of VAT to tax revenue of the government leads to greater motivation for criminals to committax evasion action against VAT. VAT can be evaded exploited in miscellaneous ways. This paper describes many kinds of VAT evasion and enforcement strategies to fight VAT Evasion in many countries and in Indonesia.